2017
DOI: 10.1016/j.chembiol.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Multifunctional Nitroreductase for Improved Activation of Prodrugs and PET Probes for Cancer Gene Therapy

Abstract: Gene-directed enzyme-prodrug therapy (GDEPT) is a promising anti-cancer strategy. However, inadequate prodrugs, inefficient prodrug activation, and a lack of non-invasive imaging capabilities have hindered clinical progression. To address these issues, we used a high-throughput Escherichia coli platform to evolve the multifunctional nitroreductase E. coli NfsA for improved activation of a promising next-generation prodrug, PR-104A, as well as clinically relevant nitro-masked positron emission tomography-imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
123
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(132 citation statements)
references
References 45 publications
8
123
1
Order By: Relevance
“…Although NTR 2.0 exhibited improved MTZ activity across all model systems, some of the other NTR variants tested over the course of this study showed less correlation across species. In addition to the lack of activity presented here for NTR 1.1 in HEK-293 cells, we have previously encountered expression instability issues for the NfsB_Ec F70A/F108Y double mutant and other native or engineered NTR variants in HCT-116 cells 23,[35][36][37] . Although not reported here, we have also been unable to generate stable transgenic zebrafish lines for several NTR variants that expressed well in both bacteria and HEK-293 cells.…”
Section: Discussionmentioning
confidence: 97%
“…Although NTR 2.0 exhibited improved MTZ activity across all model systems, some of the other NTR variants tested over the course of this study showed less correlation across species. In addition to the lack of activity presented here for NTR 1.1 in HEK-293 cells, we have previously encountered expression instability issues for the NfsB_Ec F70A/F108Y double mutant and other native or engineered NTR variants in HCT-116 cells 23,[35][36][37] . Although not reported here, we have also been unable to generate stable transgenic zebrafish lines for several NTR variants that expressed well in both bacteria and HEK-293 cells.…”
Section: Discussionmentioning
confidence: 97%
“…To analyze the activity of NfsA variants, library subsets were selected on agar plates using 0, 0.2, and 2 μg · ml −1 of niclosamide. Ninety colonies from each subset were subsequently screened via growth assays with niclosamide, metronidazole, and nitrofurantoin at 2, 10, and 5 μg · ml −1 , respectively; growth was measured via OD 600 following 4 h of incubation as previously described ( 56 ).…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the activity of NfsA variants, library subsets were selected on agar plates using 0, 0.2 and 2 μg.mL −1 of niclosamide. Ninety colonies from each subset were subsequently screened via growth assays with niclosamide, metronidazole, and nitrofurantoin at 2, 10, and 5 μg.mL −1 respectively; growth was measured via OD 600 following 4 h incubation as previously described (53).…”
Section: Methodsmentioning
confidence: 99%